ICASSP 2019 - 2019 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP) 2019
DOI: 10.1109/icassp.2019.8683158
|View full text |Cite
|
Sign up to set email alerts
|

Learning Sound Event Classifiers from Web Audio with Noisy Labels

Abstract: As sound event classification moves towards larger datasets, issues of label noise become inevitable. Web sites can supply large volumes of user-contributed audio and metadata, but inferring labels from this metadata introduces errors due to unreliable inputs, and limitations in the mapping. There is, however, little research into the impact of these errors. To foster the investigation of label noise in sound event classification we present FSDnoisy18k, a dataset containing 42.5 hours of audio across 20 sound … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
110
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(111 citation statements)
references
References 16 publications
1
110
0
Order By: Relevance
“…In contrast, only 10 % of the training set is verified: this is the data that is used to train the auxiliary classifier. It has been estimated [2] that 45 % of the unverified labels are incorrect, and that 84 % of the incorrect labels are OOD.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, only 10 % of the training set is verified: this is the data that is used to train the auxiliary classifier. It has been estimated [2] that 45 % of the unverified labels are incorrect, and that 84 % of the incorrect labels are OOD.…”
Section: Methodsmentioning
confidence: 99%
“…However, due to the uncontrolled/miscellaneous nature of these sources of data, irrelevant (OOD) instances are likely to be encountered when curating the data. For example, Freesound Annotator [6] is a platform of datasets comprised of over 260 K audio samples annotated by the public, where the authors of this platform have observed a considerable number of OOD instances [2]. OOD corruption can occur for a number of reasons, such as uncertainty in the sound (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The evaluation of the model-agnostic methods is conducted using the FSDnoisy18k dataset [5], an open dataset containing 42.5 hours of audio across 20 sound event classes, including a small amount of manually-labeled data and a larger quantity of real-world noisy data. The audio content is taken from Freesound [23], and the dataset was curated using the Freesound Annotator [24].…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, the mean absolute error equation (MAE) treats every instance equally (hence avoiding the weighting aspect), and it has been shown theoretically that MAE can be used as a loss function robust against label noise [22]. Nevertheless, MAE has been reported to cause other difficulties in training that lead to performance drop [5,14]. To take advantage of the benefits of CCE (its weighting property) and MAE (its noiserobustness), a generalization of those functions has been recently proposed in [14].…”
Section: Noise-robust Loss Functionsmentioning
confidence: 99%
See 1 more Smart Citation